Social and political transformations in Jordan: A sociological study of state-society interaction in the context of regional crises - Almazaidah, Ismail Suliman; Adwan, Rakan Abu Arabi; AlTalafeeh, Asma Sayel (Research Journal in Advanced Humanities, 2025)
This study explores the impact of regional crises, specifically the Palestinian and Syrian crises, on the social and political transformations in Jordan. It examines how these crises have shaped Jordan’s internal stability, socio-political structures, and governance. The research highlights the pivotal role of the Jordanian government in managing the repercussions of these crises through policies such as the Jordan Response Plan (JRP) and the Jordan Compact, alongside the critical contributions of civil society organizations in promoting social cohesion and supporting affected populations. Utilizing a qualitative approach, the study employs historical analysis, and thematic analysis of secondary data to provide a comprehensive understanding of the challenges Jordan has faced. The findings reveal that while Jordan has maintained relative stability amidst regional turmoil, the influx of refugees has strained its resources and heightened social tensions. These pressures underscore the urgent need for political and social reforms to address issues of governance, resource allocation, and public participation. The research concludes that strengthening partnerships between the government and civil society, enhancing democratic processes, and nurturing economic resilience are essential for ensuring Jordan’s long-term stability and sustainable development.